Investment Bank Market Share and the Performance of Acquiring Companies:: Canadian Evidence - Rasedie, Kefilwe; Srinivasan, Gopalan (Journal of Comparative International Management)

(untitled) (None, 2011)
This study examines the relationship between the investment bank market share and the performance of the companies in Canada that sought their advice as an acquirer in a merger transaction. We investigate the validity of two alternative hypotheses proposed by Rau (2000): Superior deal hypothesis and Deal completion hypothesis. The former posits that managers seek top investment advisors because of their ability to recognise the added value in their investments where as the latter have their ability to complete the deal quicker. Tobin’s Q is used as a performance measure to find out if the top quality investment banks delivered greater value to their clients compared to low quality banks. We examine the effects of time on deal performance by measuring change in Q at two different points in time – one and two years after the merger respectively. Then we investigate the effect of past performance and past market share on the current market share of a particular investment bank.